2013
DOI: 10.1186/1748-717x-8-144
|View full text |Cite
|
Sign up to set email alerts
|

An in-silico comparison of proton beam and IMRT for postoperative radiotherapy in completely resected stage IIIA non-small cell lung cancer

Abstract: IntroductionPost-operative radiotherapy (PORT) for stage IIIA completely-resected non-small cell lung cancer (CR-NSCLC) has been shown to improve local control; however, it is unclear that this translates into a survival benefit. One explanation is that the detrimental effect of PORT on critical organs at risk (OARs) negates its benefit. This study reports an in-silico comparative analysis of passive scattering proton therapy (PSPT)- and intensity modulated proton therapy (IMPT) with intensity modulated photon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 26 publications
(25 reference statements)
1
32
1
1
Order By: Relevance
“…IMPT has shown a particular ability to reduce projected complication rates in early-stage, late-stage, and postoperative patients with lung cancer. As a result, dosimetric studies for dose escalation with IMPT have shown great promise over comparative plans with 3DCRT, IMRT, and PS-PT (99,100,118,122).…”
Section: Dosimetric Studiesmentioning
confidence: 99%
“…IMPT has shown a particular ability to reduce projected complication rates in early-stage, late-stage, and postoperative patients with lung cancer. As a result, dosimetric studies for dose escalation with IMPT have shown great promise over comparative plans with 3DCRT, IMRT, and PS-PT (99,100,118,122).…”
Section: Dosimetric Studiesmentioning
confidence: 99%
“…Although, there were no improvements in dose-volume indices for lung, PSPT significantly reduced the mean radiation dose to the heart (P=0.002). Similarly, other studies have demonstrated lower doses to the heart, but suggested that lower mean lung doses and V 20 could also be achieved with improving planning and delivery techniques over time (19,20).…”
Section: Editorialmentioning
confidence: 90%
“…Each patient had evaluation of comparative PSPT and IMRT plans. If plans equally satisfied constraints on V 20 and mean lung dose, patients were randomized into either treatment group. Both groups received either 66 or 74 Gy* (relative biologic effectiveness, RBE).…”
mentioning
confidence: 99%
“…In-silico trials will facilitate the study of more difficult clinical scenarios, such as the initial testing of very expensive technologies (e.g. heavy ions), or the comparison of existing and evolved similar technology (51). Clinical trial endpoints will change from traditional metrics, such as local control, dose indices, or performance characteristics to patient-oriented endpoints, such as survival, patient reported outcomes (PRO's) and cost-effectiveness.…”
Section: Methods Of Building Evidencementioning
confidence: 99%